Regulation of the Authority to Make MPR Decrees Before and After Reforms in the 1945 Constitution of the Republic of Indonesia - Mardisontori Mardisontori; Herman Bakir (Cognitionis Civitatis et Politicae, 2024)
The People’s Consultative Assembly (MPR) is a high state institution in the Indonesian constitutional system and MPR Decrees are one type of applicable legislation. The legal basis for MPR Decrees before the amendment to the 1945 Constitution can be found through the interpretation of some articles in the 1945 Constitution. After the amendment to the 1945 Constitution, apart from changing the position of the MPR as the highest state institution, it also changed the duties and authority of the MPR. The MPR no longer issues MPR Decrees. However, based on Law Number 12 of 2011 concerning the Formation of Legislative Regulations, it places MPR Decrees in the sequence of statutory regulations. Thus, the MPR Decree is part of the types and hierarchy of statutory regulations placed under the 1945 Constitution of the Republic of Indonesia. This article raises the issue of how the authority to make MPR Decrees is regulated before and after the amendments to the 1945 Constitution and is linked to TAP MPR RI Number I/MPR/2003 concerning Review of the Material and Legal Status of TAP MPRS and TAP MPR RI from 1960 to 2002. The purpose of this writing is to find out how the authority to make MPR Decrees is regulated before and after the amendment to the 1945 Constitution and is linked to TAP MPR RI Number I/MPR/2003. This writing uses a normative juridical method with a statutory regulatory approach. With some MPR Decrees still in effect before and after the reform, they are based on constitutional practices as well as the provisions in the 1945 Constitution and related laws and regulations.